Tawassul Dengan Roh Para Wali: Huraian dan Ulasannya - Daud, Zakaria @ Mahmod (Jurnal Usuluddin, 1996)
This article tries to identify tawassul bi ruh al-Wali. References are made to the teaching of various mazhab and the opinion of their ulama.